Kentucky Foreign Language Quarterly. University of Kentucky at Lexington: tomo 1 (1954), tomo 2 (1955). - Vergara, M. A. (El Colegio de México, 1957)
Se reseñó: Kentucky Foreign Language Quarterly: tomo 1 (1954), tomo 2 (1955).